2012
DOI: 10.1155/2012/532862
|View full text |Cite
|
Sign up to set email alerts
|

Palm Tocotrienol Supplementation Enhanced Bone Formation in Oestrogen-Deficient Rats

Abstract: Postmenopausal osteoporosis is the commonest cause of osteoporosis. It is associated with increased free radical activity induced by the oestrogen-deficient state. Therefore, supplementation with palm-oil-derived tocotrienols, a potent antioxidant, should be able to prevent this bone loss. Our earlier studies have shown that tocotrienol was able to prevent and even reverse osteoporosis due to various factors, including oestrogen deficiency. In this study we compared the effects of supplementation with palm toc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 20 publications
(27 reference statements)
4
37
0
1
Order By: Relevance
“…The results of the structural histomorphometric analysis suggest that tocotrienols prevent bone resorption by reducing the trabecular perforation that typically occurs during estrogen deficiency. We also reported that palm tocotrienols significantly improved bone dynamic parameters in estrogen-deficient rats by increasing the mineralizing surface, the mineral apposition rate and the bone formation rate (17). The effects of tocotrienol on dynamic parameters indicate that this form of vitamin E has anabolic properties that result in increased bone formation.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the structural histomorphometric analysis suggest that tocotrienols prevent bone resorption by reducing the trabecular perforation that typically occurs during estrogen deficiency. We also reported that palm tocotrienols significantly improved bone dynamic parameters in estrogen-deficient rats by increasing the mineralizing surface, the mineral apposition rate and the bone formation rate (17). The effects of tocotrienol on dynamic parameters indicate that this form of vitamin E has anabolic properties that result in increased bone formation.…”
Section: Discussionmentioning
confidence: 94%
“…Chin et al demonstrated that annatto tocotrienol at 60 mg/kg for eight weeks specifically increased the expression of bone formation genes coding for alkaline phosphatase, collagen type I alpha 1, osteopontin and beta-catenin in orchidectomized rats [29]. In an osteopenic model due to estrogen deficiency, palm tocotrienol at 60 mg/kg for two months increased the mineral apposition rate and bone formation rate in rats [40,41]. Gamma-tocotrienol and palm tocotrienol-rich fraction at 60 mg/kg for two months was able to exert similar actions in a bone loss model due to nicotine in male rats [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had been performed previously using γTT-predominant palm-derived tocotrienol mixtures containing 20%–30% αTF to investigate the antiosteoporotic effects of tocotrienol 10. The majority of these studies found that palm-derived tocotrienols at 60 mg/kg body weight were effective in preventing degenerative changes in structural, dynamic, cellular and static indices of bone in osteoporosis induced by estrogen deficiency,12–14 nicotine,16 and free radicals 15. In a study using normal rats, isomers of tocotrienol were found to have anabolic effects on bone as evaluated by biomechanical strength testing and histomorphometric evaluation 23.…”
Section: Discussionmentioning
confidence: 99%